Strongly nonparabolic variation of the band gap in InxAl1−xN with low indium content. (14th December 2015) - Zubialevich, Vitaly Z; Dinh, Duc V; Alam, Shahab N; Schulz, Stefan; O'Reilly, Eoin P; Parbrook, Peter J
Abstract: 80–120 nm thick In x Al1− x N epitaxial layers with 0 < x < 0.224 were grown by metalorganic vapour phase epitaxy on AlN/Al2 O3 -templates. The composition was varied through control of the growth temperature. The composition dependence of the band gap was estimated from the photoluminescence excitation absorption edge for 0 < x < 0.11 as the material with higher In content showed no luminescence under low excitation. A very rapid decrease in band gap was observed in this range, dropping down below 5.2 eV at x = 0.05, confirming previous theoretical work that used a band-anticrossing model to describe the strongly x -dependent bowing parameter, which in this case exceeds 25 eV in the x → 0 limit. A double absorption edge observed for InAlN with x < 0.01 was attributed to crystal-field splitting of the highest valence band states. Our results indicate also that the ordering of the valence bands is changed at much lower In contents than one would expect from linear interpolation of the valence band parameters. These findings on band gap bowing and valence band ordering are of direct relevance for the design of InAlN-containing optoelectronic devices.